Mexico: a civil-military “pact” unravelling? - Hachemer, Peter (Reforming Civil-Military Relations in New Democracies, 2017)
Mexico’s civil-military relations were extraordinary stable during authoritarian rule: installed as a pillar of the PRI’s control, the military never intervened into civilian politics or threatened to overthrow the regime. On the contrary, military leaderships almost unconditionally defended the regime against internal threats, thereby repeatedly taking the blame for civilian mismanagement. Coinciding with the intensifying US-led “War on Drugs”, the transition to democracy threatened to destabilize this balance and lead to open opposition within the military. Deemed the “biggest loser” in the “War on Drugs” by analysts, the armed forces have repeatedly claimed themselves unfit for the task and called on civilian leaders to improve law enforcement efforts. The analysis finds, however, that the feared “control gap” anticipated after the end of PRI rule did not materialize; instead, the tried and tested “pact” has come under severe strain in the new millennium.
Gesehen am 05.12.2016